Evaluation of the Effectiveness of Post-Pandemic MSME Tax Incentives on Local Economic Performance - Loso Judijanto (PT. Anagata Sembagi Education, 2025)
This study evaluates the effectiveness of post-pandemic tax incentives for micro, small, and medium enterprises in Indonesia and examines their impact on local economic performance. Using a combined conceptual and policy analysis approach, the research assesses how behavioural, structural, and institutional factors mediate the ability of MSMEs to convert tax relief into meaningful economic outcomes. The findings indicate that MSME responses to tax incentives are strongly influenced by business formality, liquidity constraints, digital readiness, sectoral composition, and information accessibility. Regions with stronger administrative capacity, higher digitalization, and greater purchasing power demonstrate more substantial improvements in employment recovery, business reopening rates, and local consumption. Structural factors such as regulatory clarity, financial inclusion, supply chain integration, human capital quality, and infrastructure development further shape the sustainability of tax incentive impacts. The study concludes that while tax incentives play an important role in supporting MSME recovery, their long-term effectiveness depends on broader institutional reforms that enhance administrative capability, promote digital access, strengthen financial systems, and improve local governance. Strengthening these structural conditions will expand the capacity of MSMEs to benefit from fiscal incentives and contribute to more resilient and inclusive local economic growth.